ANALYSIS OF CYCLE 8 PERIOD FLYING STAR FENG SHUI ON CYCLE 7 PERIOD RESIDENTIAL SPACE LAYOUT - Liman (Jurnal Riset Arsitektur, 2019)
Abstract- Flying Star Feng Shui is one of many Feng Shui form using compass method. Flying Star Feng Shui uses Lo Shu Square with constantly changing number on each palaces for every periods, unlike traditional Lo Shu Square which has been used for thousands of years. The concept of Flying Star Feng Shui lies on dynamic principle of time which changes the luck of a person. The objects on this study is a few houses in Bandung City which is built in cycle 7 period (1984 – 2003).The methods used to analyze this study is qualitative descriptive, which the writer observe each of the objects directly and analyze them using 2 reference books. David Twicken’s Flying Star - Feng Shui Made Easy and Vincent Koh’s Basic Science of Feng Shui.In the end of this study, the conclusion is Flying Star Feng Shui surely can influence the life of the people living in the house. Some events in their life in cycle 8 can be foreseen by Flying Star Feng Shui, such as robbery, lawsuits, and illness.. Key Words: Flying Star Feng Shui, Houses, Events in the life of house users.